BioDSL: A Domain-Specific Language for mapping and dissemination of Biodiversity Data in the LOD - Serique, Kleberson J. do A.; dos Santos, José L. Campos; Moreira, Dilvan A. (Anais do Brazilian e-Science Workshop (BreSci); 2016: Anais do X Brazilian e-Science WorkshopDO - 10.5753/bresci.2016.10011, 2016)
Currently, Linked Open Data (LOD) have enabled integrated data sharing across disciplines over the Web. However, for LOD users, in areas such as biodiversity (which massively use the Web to disseminate data), the task of transforming data file contents in CSV (Comma Separated Value) to RDF (Resource Description Framework) is not trivial. We have developed a new approach to map data files in CSV to RDF format based on a domain-specific language (DSL) called BioDSL. Using it, biodiversity data users can write compact programs to map their data to RDF and link them to the LOD. Biodiversity vocabularies and ontologies, such as Darwin Core and OntoBio, can be used with BioDSL to enrich user data. Existing tools are exclusively focused on mapping (CSV to RDF), offering little or no support for linking data to the LOD (interconnecting user entities to LOD entities). They also are more complex to use than BioDSL.